Study of the Efficacy of Different Concentrations of Alcohol-Based Hand Sanitizer in Preventing Pathogen Transmission Through Palms - Ekawati, Evy Ratnasari; Santoso, Setyo Dwi; Pradana, Muhammad Sungging; Santoso, Andreas Putro Ragil; Hanum, Mufida; Khoir, Intan Wahyunillah Zaidah; Arifina, Rosyidatul (Biota, 2024)
An integral part of the human body is the hands, which most frequently come into contact with various items; they can be an intermediary for spreading infections from hands to food and potentially eaten by humans. Maintaining hand hygiene is the right strategy to avoid this spread, which includes using an alcohol-based hand sanitizer. This study examines the potential for varying concentrations of alcohol-based hand sanitizer to transmit pathogens through the palms. The form of research is a laboratory experiment with an appropriate research design. Test the antibacterial potential of variations in alcohol-based hand sanitizer concentrations of 40, 50, 60, 70, and 70% using well diffusion and dilution methods. The tests were done in quadruplicates. The test bacteria used are Escherichia coli, Enterotoxigenic Escherichia coli, Salmonella typhimurium, Pseudomonas aeruginosa, Klebsiella pneumoniae, and Staphylococcus aureus. The results of the research showed that of the four variations in the concentration of alcohol-based hand sanitizer, the bacteriostatic ability against Salmonella typhimurium, Pseudomonas aeruginosa, and Klebsiella pneumoniae bacteria was at a concentration of 40% to 80%. The bactericidal activity at a concentration of 80% was demonstrated by Escherichia coli, Enterotoxigenic Escherichia coli, and Staphylococcus aureus. Bactericidal activity was demonstrated against Escherichia coli, Enterotoxigenic Escherichia coli, and Staphylococcus aureus at an 80% concentration.